A look-up table based approach to characterize crystal twinning for synchrotron X-ray Laue microdiffraction scans - Li, Yao (Journal of applied crystallography, 2015)
An automated method has been developed to characterize the type and spatial distribution of twinning in crystal orientation maps from synchrotron X-ray Laue microdiffraction results. The method relies on a look-up table approach. Taking into account the twin axis and twin plane for plausible rotation and reflection twins, respectively, and the point group symmetry operations for a specific crystal, a look-up table listing crystal-specific rotation angle-axis pairs, which reveal the orientation relationship between the twin and the parent lattice, is generated. By comparing these theoretical twin-parent orientation relationships in the look-up table with the measured misorientations, twin boundaries are mapped automatically from Laue microdiffraction raster scans with thousands of data points. Taking advantage of the high orientation resolution of the Laue microdiffraction method, this automated approach is also applicable to differentiating twinning elements among multiple twinning modes in any crystal system